PENGARUH PENERAPAN KAIZEN TERHADAP KINERJA PEGAWAI DINAS PARIWISATA DAN KEBUDAYAAN GERBANGKERTOSUSILA - Wahyu Eko Pujianto; Ahmad Riyadh U. Balahmar (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2014)
Research is aimed to present the influence of the application of kaizen against the employee performance of tourism and culture gerbangkertosusila. Population in this research all of its culture and tourism dept. gerbangkertosusila 73 people, which amounted to and techniques of the sample in this research using a sample of the census. The, technique of collecting data obtained by the spread of kuisioner. The technique of linear regression analysis used f double by test and test it t as a test of an hypothesis.The results of tests indicating that the implementation of kaizen impact on the performance of employees of tourism and culture gerbangkertosusila. It showed that the better the application of kaizen to be implemented on culture and tourism dept. gerbangkertosusila will be able to improve the performance of tourism and culture gerbangkertosusila. The greater attention to the needs of company employees and the company will get reciprocal appropriate, namely productivity work yet.